BRICS: Brick by Brick to be an Alternative Global Framework (?) - Genisa, Fathania Queen; Waskito, Wasis (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2025)
BRICS is an important emerging power that has gradually caught international attention. There have been several breakthroughs done by BRICS that made the existing dominant powers turn their head towards BRICS, the United States, for example. Throughout their annual summit, they persistently resonate with the importance of being more representative and inclusive in the context of world order. On the other hand, as an entity, it is still considered nebulous; some say it is a forum, a strategic partnership, and officially called itself an informal group of states as written on the BRICS’ website. It raises the question of how BRICS can pursue a substantial goal of becoming an alternative global framework when it is still considered a nebulous entity. Instead of analyzing it through economic context as many studies on BRICS have done, the authors use the inclusive governance principles - a recent concept in understanding global order - to analyze BRICS’ capability to become an alternative global framework.